Carbohydrate-Derived Polytriazole Nanoparticles Enhance the Anti-Inflammatory Activity of Cilostazol - Rivas, Maria Veronica (2022)
Poly(amide-triazole) and poly(ester-triazole) synthesized from d-galactose as a renewable resource were applied for the synthesis of nanoparticles (NPs) by the emulsification/solvent evaporation method. The NPs were characterized as stable, spherical particles, and none of their components, including the stabilizer poly(vinyl alcohol), were cytotoxic for normal rat kidney cells. These NPs proved to be useful for the efficient encapsulation of cilostazol (CLZ), an antiplatelet and vasodilator drug currently used for the treatment of intermittent claudication, which is associated with undesired side-effects. In this context, the nanoencapsulation of CLZ was expected to improve its therapeutic administration. The carbohydrate-derived polymeric NPs were designed taking into account that the triazole rings of the polymer backbone could have attractive interactions with the tetrazole ring of CLZ. The activity of the nanoencapsulated CLZ was measured using a matrix metalloproteinase model in a lipopolysaccharide-induced inflammation system. Interestingly, the encapsulated drug exhibited enhanced anti-inflammatory activity in comparison with the free drug. The results are very promising since the stable, noncytotoxic NP systems efficiently reduced the inflammation response at low CLZ doses. In summary, the NPs were obtained through an innovative methodology that combines a carbohydrate-derived synthetic polymer, designed to interact with the drug, ease of preparation, adequate biological performance, and environmentally friendly production.